Performance-based fire safety design - Hurley, Morgan J.; Rosenbaum, Eric R. (CRC Press, 2015)
Master an Approach Based on Fire Safety Goals, Fire Scenarios, and the Assessment of Design AlternativesPerformance-Based Fire Safety Design demonstrates how fire science can be used to solve fire protection problems in the built environment. It also provides an understanding of the performance-based design process, deterministic and risk-based analysis techniques, development of design fire scenarios, trial design development and analysis, and building lifecycle management.